Analysis of Carbon Monoxide (CO) Emission Dispersion Using AERMOD Modeling Along Tandes Street - Abrar Athaya Yuris Erbinavydho; Okik Hendriyanto Cahyonugroho (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The increase in motor vehicle activity along Tandes Street to Raya Manukan Kulon Street, Surabaya, has the potential to reduce air quality due to carbon monoxide (CO) emissions. This study analysed the dispersion of CO using the AERMOD modelling system and direct field measurements at several observation points. The modeling results showed a maximum CO concentration of 14,972 µg/m³, while field measurements reached 16,749 µg/m³. Model validation using the Root Mean Square Percent Error (RMSPE) method produced a value of 19.23%, indicating that the AERMOD model has good accuracy in representing actual field conditions. The differences between simulation and observation results were influenced by meteorological conditions, traffic variations, and input data uncertainty. Overall, traffic activity significantly affects CO concentrations in the study area, although these concentrations remain within applicable air quality standards. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well BeingSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate Action